1999
DOI: 10.1002/stem.170107
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Adult Human Bone Marrow by Factors Secreted by Fetal Liver Hematopoietic Cells: In Vitro Evaluation Using Semisolid Clonal Assay System

Abstract: Fetal liver infusion (FLI) therapy has been used in various disorders, such as aplastic anemia, leukemia, metabolic disorders, etc., and has been shown to result in stimulation of autologous hematopoiesis in many cases. The aim of the present study was to elucidate the mechanism of stimulation of adult hematopoiesis by fetal liver hematopoietic cells (FLHC) and to identify the factors involved in the process using a clonal assay system in vitro. The effect of FLHC on the clonal growth of bone marrow cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The mechanism(s) responsible for the higher cycling rates that we observed in CD34+ cells from fetal marrow compared with those of adult marrow are unclear. These differences might reflect properties unique to the fetal hematopoietic microenvironment [11], such as a differing proportion of stimulatory factors [12] or hematopoietic inhibitors [13]. Alternatively, fetal progenitors might possess cell cycle characteristics that are intrinsically different from those of their adult counterparts [14].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism(s) responsible for the higher cycling rates that we observed in CD34+ cells from fetal marrow compared with those of adult marrow are unclear. These differences might reflect properties unique to the fetal hematopoietic microenvironment [11], such as a differing proportion of stimulatory factors [12] or hematopoietic inhibitors [13]. Alternatively, fetal progenitors might possess cell cycle characteristics that are intrinsically different from those of their adult counterparts [14].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, in these studies, nanogram concentrations of TGF-β1 have been used; secondly, the effect is either studied on a cell line or on erythroid progenitors; thirdly, our protocol is distinct from the reported ones; The effect of TGF-β1 on cell proliferation and differentiation depends on its concentration and the cell type used. Earlier, it was reported that TGF-β1 at low concentration (10-20 pg/ml) significantly stimulated colony formation from HSCs, indicating that these progenitors are the direct target of stimulatory action of TGF-β1, whereas at high TGF-β1 concentration (5-10 ng/ml) it inhibited colony formation [16,17,38]. Here, we show, for the first time, that low concentration of TGF-β1 is more effective on erythroid differentiation of HSCs.…”
Section: Discussionmentioning
confidence: 97%
“…Wang, Dong, et al, 2018). However, a consistent association of TGFβ1 with the hematopoietically active sites such as bone marrow niche, second trimester foetal liver and the hematopoietic islands of the yolk sac (Kale & Limaye, 1999;Schmid, Cox, Bilbe, Maier, & McMaster, 1991) point towards a possibility that perhaps it could have an as yet unidentified positive regulatory role in hematopoiesis.…”
mentioning
confidence: 99%